2020
DOI: 10.1021/acs.orglett.0c02618
|View full text |Cite
|
Sign up to set email alerts
|

Iodonium Ylides as Carbene Precursors in Rh(III)-Catalyzed C–H Activation

Abstract: The rhodium­(III)-catalyzed coupling of C–H substrates with iodonium ylides has been realized for the efficient synthesis of diverse cyclic skeletons, where the iodonium ylides have been identified as efficient and outstanding carbene precursors. The reaction systems are applicable to both sp2 and sp3 C–H substrates under mild and redox-neutral conditions. The catalyst loading can be as low as 0.5 mol % in a gram-scale reaction. Representative products exhibit cytotoxicity toward human cancer cells at nanomola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 44 publications
0
58
0
Order By: Relevance
“…Herein, iodonium ylides utilized as a carbene precursors in Rh(III)‐catalyzed C−H functionalization's (Scheme 34). [48] …”
Section: C−h Alkenylation With Carbene Precursorsmentioning
confidence: 99%
“…Herein, iodonium ylides utilized as a carbene precursors in Rh(III)‐catalyzed C−H functionalization's (Scheme 34). [48] …”
Section: C−h Alkenylation With Carbene Precursorsmentioning
confidence: 99%
“…1 H NMR spectra were recorded at room temperature on a Bruker AVANCE NEO 400 MHz Digital NMR spectrometer and were reported relative to residual CDCl 3 (δ 7.26 ppm). 13 C NMR spectra were recorded on a Bruker AVANCE NEO 400 MHz Digital NMR spectrometer (100 MHz) and were reported relative to CDCl 3 (δ 77.16 ppm). Data for 1 H NMR were reported as follows: chemical shift (δ ppm) (multiplicity, coupling constant (Hz), integration).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Multiplicities were reported as follows: s = singlet, d = doublet, t = triplet, q = quartet, m = multiplet, br s = broad singlet. Data for 13 C NMR and 19 F NMR were reported in terms of chemical shifts (δ ppm). High-resolution mass spectra (HRMS) were obtained by use of a Bruker Compact TOF mass spectrometer in electrospray Unless otherwise noted, all chemicals were purchased.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2007, Jenks et al developed C,S-sulfonium ylides based on the thiophene moiety as a useful precursor for carbenes using a photochemical activation methodology (Scheme 1a) [9]. The synthesized sulfonium ylides were stable, easy to handle, and could generate free carbenes using ultraviolet (UV) irradiation without a catalyst [10,15,17]. These studies reported that onium ylides with relatively large conjugated systems could photochemically generate the corresponding carbene species.…”
Section: Introductionmentioning
confidence: 99%